Adsorption and Stability Properties of Aqueous Suspension of Chromium (III) Oxide in the Presence of Synthetic and Natural Polymers: Possibilities of Solid Removal - Małgorzata Wiśniewska; Iwona Ostolska; Katarzyna Szewczuk-Karpisz; Agnieszka Nosal-Wiercińska (Adsorption Science & Technology, 2015)
The effects of type and content of polymer functional groups on the adsorption mechanism on the chromium (III) oxide surface were studied. Both synthetic [poly(acrylic acid) (PAA), anionic polyacrylamide (PAM), poly(aspartic acid) (ASP), block co-polymer of ASP with poly(ethylene glycol) (ASP-b-PEG)] and natural [bovine serum albumin, ovalbumin, human serum albumin, bacterial polysaccharide (exopolysaccharide EPS)] polymers were applied. For this purpose, adsorption, surface charge, zeta potential and stability measurements were carried out. The largest adsorption was found for the ASP-b-PEG (synthetic polymer) and EPS (natural polymer). The most effective destabilizers for Cr 2 O 3 removal from the aqueous suspension were PAA 240,000 and ASP 6800.